The Vianés and the Galician Language of the Area of Zamora. Particularities in Common of these Varieties of Eastern Galician Language - Álvarez Pousa, Concepción (Madrygal. Revista de Estudios Gallegos, 2019)
The objective of this article is to make known the "ourensana" linguistic variety of the Land of Viana do Bolo, the Vianés, and the varieties of Galician language of the Zamora area that is composed by ourensán dialect of the A Mezquita, and the Zamora dialects of the As Portelas, which belong to eastern Galician language. After the first approach to these territories, will be deeped in the linguistic characterisation of the varieties which had been mentioned below to detail of the Vianés particularities, given its proximity, it possess concerning the neighboring dialects of the area of Zamora. Moreover, it will be dealing with the sociolinguistic situation of the area that it has been said and it will be supported with the phonetic transcriptions of oral samples which belong to Vianés and the area of Zamora. Regarding the results, it is concluded that the Vianés, belonging to the eastern-central area shares several dialectal features with the Galician varieties of the area of Zamora, both areas belong to the eastern Galician, mainly in areas such as phonetics and morphosyntax.